Novel Functional Materials Based on Cellulose - Qi, Haisong (Springer International Publishing : Imprint: Springer, 2017)
This Brief presents a review of new eco-friendly processes, design and applications for novel cellulose-based materials, including regenerated materials, composites, nanocellulose and cellulose derivatives. Application of these materials in smart textiles, packaging, energy storage, sensors, gas separations, tissue engineering and drug release are highlighted. .
Keywords: Materials science.; Renewable energy resources.; Polymers.; Renewable energy sources.; Alternate energy sources.; Green energy industries.; Biomaterials.; elektronické knihy; electronic books